Desarrollo de una aplicación android para el control de un dispositivo móvil usando arquitectura cliente-servidor - Novoa Ruiz, Pedro Luis (2017)
The research work has the objective of control of a mobile device in a working_x000D_ environment, through the development of an Android application with the support_x000D_ of a server and a storage database. The control is carried out with data logging_x000D_ and remote execution of actions on the device. With regard to the data include_x000D_ information on the hardware, software, and other features. Also, at the same time_x000D_ run active and automated functions that respond to events of changes and interaction_x000D_ from the server, performing an exchange of data, such as messages, inventories or_x000D_ reports in general._x000D_ For communication use was made of the client-server architecture based on_x000D_ RMI (Remote Method Invocation) and an implementation of Java RMI. In addition_x000D_ to the use of FCM (Firebase Cloud Messaging) as a secondary communication._x000D_ The stage of development and testing of the mobile application, was based on_x000D_ the changes of Android versions and in the functions of support for versions 4_x000D_ onwards, making possible its implementation directed to devices of type phones_x000D_ and tablets; thus, obtaining good results in the actions and events set for the control